Two-stage hepatectomy aiming for the development of intrahepatic venous collaterals for multiple colorectal liver metastases - Harufumi Maki; Shouichi Satou; Kentaro Nakajima; Atsuki Nagao; Kazuteru Watanabe; Hitoshi Satodate; Satoshi Nara; Kaoru Furushima; Yasushi Harihara (Surgical Case Reports)
Abstract Background Aggressive hepatectomy with venous resection has a higher risk of postoperative liver failure (POLF) than hepatectomy without venous reconstruction; however, venous reconstruction is technically demanding. We performed a novel two-stage hepatectomy (TSH) without venous reconstruction in a patient with bilobar multiple colorectal liver metastases located near the caval confluence, waiting for the development of intrahepatic venous collaterals between procedures. Case presentation A 60-year-old man was referred to our hospital with sigmoid colon cancer accompanied by intraabdominal abscess and two synchronous liver metastases. One of the liver tumors (tumor 1) was located in segment 8 near the caval confluence and was attached to both the right hepatic vein (RHV) and middle hepatic vein (MHV). The other tumor (tumor 2) in the left lobe invaded the umbilical portion of the portal vein. Both liver metastases decreased in size after four cycles of panitumumab/5-fluorouracil, leucovorin, and oxaliplatin (FOLFOX) therapy. Radical liver resection was planned because tumor 1 had not invaded the MHV. However, three-dimensional volumetric software showed that the non-congested volume of the future liver remnant was estimated at 354 ml, which corresponded to 26.3% of the total liver volume. TSH was scheduled to avoid POLF. We first performed limited resection of segment 8 with resection of the RHV root. After the first hepatectomy, the development of intrahepatic venous collaterals between the RHV and MHV was seen on computed tomography and magnetic resonance imaging. The estimated non-congested future liver remnant was 1242 ml, 78.5% of the total liver volume. Therefore, the patient underwent left hemihepatectomy 58 days after the first hepatectomy. We saw no adhesions around the porta hepatis, and the left hepatic artery and left branch of the portal vein were safely exposed and divided. Intraoperative Doppler ultrasonography revealed intrahepatic venous collaterals arising from RHV to MHV. The patient’s postoperative course was uneventful, and he underwent eight cycles of panitumumab/FOLFOX therapy for 5 months after the second hepatectomy. Conclusions Our TSH strategy helped avoid POLF by waiting for the development of intrahepatic venous collaterals.